PECULIARITIES OF MANIFESTATIONS OF COMMUNICATIVE TOLERANCE OF STUDENTS IN THE CONDITIONS OF QUARANTINE INSULATION - Chuyko, Halyna; Chaplak, Yan; Komisaryk, Mariya (Інститут психології імені Г.С. Костюка НАПН України, 2022)
The article deals with the theoretical analysis and empirical research of psychological features of the phenomenon of communicative tolerance in the conditions of quarantine isolation. Different understandings of the concept of tolerance / communicative tolerance and its structure by scientists in the scientific psychological literature are considered. It was found that most scientists, analyzing the meaning of the concept of "communicative tolerance", often describe it as: personal characteristic; attitude to another person and the corresponding behavior of a person in the communication process. And in the structure of communicative tolerance they more often distinguish cognitive, affective and behavioral components, or offer a list of qualities of a tolerant personality. The understanding of communicative tolerance as a sophisticated complex holistic psychological phenomenon based on person’s communicative experience, their morality, inner culture and upbringing, as well as on the development of such personal traits as: benevolence, politeness, sociability, empathy, courtesy, moderation, on tendency to solve existing problems through cooperation, agreements and taking into account the interests of both sides of the communication – is generalized. It is stated that in the attempts of modern scientists to understand and explain the concept of tolerance in communication, we can distinguish two main approaches: linguistic and psychological, – which are partially opposed to each other. The first is by emphasizing that "communicative tolerance" is purely communicative category because it manifests itself in communication, and the second is by arguing that communicative tolerance is a complex and multifaceted mental phenomenon. It is noted that in the word combination "communicative tolerance" the concept of "communicative" – is just an attribute of the main word – "tolerance", emphasizing its psychological understanding. Peculiarities of development and manifestation of communicative tolerance in first- and second-year students, future psychologists, for whom it is a professionally important quality, was studied. It was found that respondents mainly tend to show the competent position in communication and to comprehensive accept other people, but the degree of their tolerance in communication was insufficient, because they could not hide their own negative emotions and communicative experience; may show indisputability, aggression or cruelty to the interlocutor; aspire to change him by fiting to their own image; didn’t want to get closer to another person on an emotional basis for the sake of effective communication. The correlations between the indicators of the techniques of diagnostics of communicative tolerance and other methods, the existence of which confirms the sophisticated, complexity and multifaceted nature of the phenomenon of communicative tolerance; factors that discover the hidden behind the correlation of the reasons for intolerance of respondents in communication and the ineffectiveness of its results are analyzed. It is concluded that tolerant communication is based on the conscious acceptance of another person's individuality; the desire to listen, to understand her, without suppressing the freedom of her expression and without aspire to change in her own way; the wish to communicate sincerely and openly, showing kindness and respect to human dignity and restrain possible negative feelings; on the desire to cooperate in order to avoid conflicts and achieve successful, effective and efficient communication.
Keywords: tolerance, communicative tolerance, interpersonal communication, communicative competence, acceptance of another, emotional barrier in communication